Usually, quadratic equations equal 0, and to find the solution you need to make x equal the value that, when added or subtracted to the rest of its bracket, makes 0. This means that your answer is (x + 5)(x - 2) = 0, because 5 - 5 = 0 and 2 - 2 = 0. I hope this helps! Let me know if you would like me to explain further :)
Add 3 on both sides of the equation
3x=0
divide 3 on both sides of the equation
x=0
Answer:
Answers below
Step-by-step explanation:
Marion: 42 inches
Elijah: 38 inches
Lorie: 57 inches
Convert each to inches and solve.
Hope this helps!
Answer:
36
Step-by-step explanation:
Flip your eq. x/3 + 6 = 18.
Solve (Number on one, variable on other)
+6 -6 = 0. 18-6=12.
Multiply.
12 * 3 = 36.
Answer:
See below
Step-by-step explanation:
5) y = x + 7
6) y = -x + 1